2014
DOI: 10.1016/j.jisa.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Implementing and evaluating a software-independent voting system for polling station elections

Abstract: In 2009 the German Federal Constitutional Court introduced the principle of "public nature of elections" [1]. This principle requires that when using electronic voting systems it must be possible for the citizen to verify the essential steps in the election process and in the ascertainment of the results reliably and without special expert knowledge. Unfortunately, none of the existing systems complies with this principle. As a result, the use of electronic voting systems in Germany for parliamentary elections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 4 publications
0
12
1
Order By: Relevance
“…The percentage of participants that have privacy concerns is smaller compared to the study conducted by Budurushi et al [3], 21% v.s. 39.9% respectively, however not sufficient in the context of electronic voting.…”
Section: Discussion and Future Workcontrasting
confidence: 63%
See 4 more Smart Citations
“…The percentage of participants that have privacy concerns is smaller compared to the study conducted by Budurushi et al [3], 21% v.s. 39.9% respectively, however not sufficient in the context of electronic voting.…”
Section: Discussion and Future Workcontrasting
confidence: 63%
“…The studies conducted by Budurushi et al [3] and Llewellyn et al [10] showed that voters have concerns regarding privacy of their votes, when PATs containing information other than the plaintext vote are used [3] and [10]. Llewellyn et al [10] conducted a user study at the University of Surrey, UK in June/July 2011.…”
Section: Privacy Concerns In Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations